Integrated approach of network pharmacology, molecular docking, and clinical observations in evaluating the efficacy and safety of Bufei Huoxue capsules for pulmonary hypertension associated with chronic obstructive pulmonary disease - Wenjun He; Chunli Liu; Xuanyi Li; Bihua Zhong; Qian Jiang; Ning Lai; Yuanhui Xiong; Weici Feng; Yilin Chen; Dansha Zhou; Defu Li; Wenju Lu; et al. (Pulmonary Circulation)
Abstract Chronic obstructive pulmonary disease (COPD) is a persistent and progressive disorder characterized by airway or alveolar abnormalities, commonly leading to pulmonary hypertension (PH). This clinical observational study investigates the therapeutic mechanisms of Bufei Huoxue capsules (BHC) in treating PH in patients with COPD‐linked PH (COPD‐PH) using network pharmacology and molecular docking methods, and assesses the therapeutic efficacy and safety of BHCs. The active compounds and their target proteins in BHCs were sourced from the Traditional Chinese Medicine Systems Pharmacology database, with additional target proteins derived from the GeneCards and OMIM databases. An active network was constructed using Cytoscape 3.7.1, and interaction networks were established. Intersecting targets underwent Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis using the Metascape database. Network pharmacology and molecular docking studies demonstrated favorable binding affinities of BHC active ingredients, such as quercetin, bavachalcone, and isobavachin, for key targets including PTGS1, ESR1, and PTGS2. Gene Ontology enrichment analysis highlighted the involvement of these targets in processes such as the positive regulation of locomotion, the transmembrane receptor protein tyrosine kinase signaling pathway, and peptidyl‐tyrosine phosphorylation. KEGG pathway analysis indicated their roles in pathways related to cancer, AGE‐RAGE signaling in diabetic complications, and prostate cancer. BHCs exhibit therapeutic effects on COPD‐PH through multi‐component, multi‐target, and multi‐pathway interactions. This clinical observational study confirms the efficacy and safety of BHCs in improving cardiac and pulmonary functions, enhancing exercise tolerance, and elevating the quality of life in patients with COPD‐PH.